Topmix Permeable : An eco-friendly Innovation to tackle Flooding in Urban Areas - Fairus Salimi (Journal of Software Engineering, Information and Communication Technology (SEICT), 2023)
Flooding is a natural disaster that has occurred most often in indonesia since long ago, especially in the rainy season. the consequences of this flood can be a disaster that causes risks that adversely affect the community. Therefore as one of the solutions to water absorption on a small amount of land and high rainfall resulting in flooding, an innovation in manufacturing in the field of environmentally friendly construction was developed, namely Topmix Permeable asphalt. topmix permeable asphalt is called porous asphalt. This porous asphalt has larger pores than normal asphalt. with a porous surface, it allows water to flow and dissipate naturally into the soil. this research method is obtained from literature studies, data analysis so that the conclusion is obtained from the innovation of environmentally friendly permeable topmix asphalt to prevent flooding. porous asphalt innovations that are effective and efficient in workmanship and cost, make environmentally friendly asphalt that can store water in the ground and reduce the risk of flooding, especially in urban areas.